Peran Guru Pendidikan Agama Kristen Dalam Meningkatkan Prestasi Belajar Peserta Didik Di SMP Negeri 3 Sompak Kecamatan Sompak Kabupaten Landak - Yosua Jupianto; Ridolfroa S. Th Manggoa; Esau Yesyurun Tang; Marthen Mau (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
PAK teachers as individuals play an important role in improving student learning achievement. To improve learning achievement, PAK teachers must also play an active role in schools, in educating, teaching, directing and arousing students' enthusiasm for learning. Then PAK teachers should find out what causes students to be less interested in learning, thereby causing a decline in students' learning achievement. Lack of awareness of students' learning in learning: namely the lack of special attention from PAK teachers, the students' environment at school, and the students' environmental habits, so that students are still at school. The aim of writing this scientific work is to determine the role of PAK teachers in improving student learning achievement at SMP Negeri 3 Sompak. The research methodology used is qualitative, literature study, observation and interviews. Students need to improve their learning achievements, so they can get good results. To get good results in learning, the attention of PAK teachers is needed in encouraging students to study actively.